2014
DOI: 10.1074/jbc.m114.588111
|View full text |Cite
|
Sign up to set email alerts
|

Specific Phosphorylations Transmit Signals from Leukocyte β2 to β1 Integrins and Regulate Adhesion

Abstract: Background:Integrins regulate leukocyte adhesion in a stepwise manner. Results: ␤ 2 Integrins can signal to ␤ 1 integrin very late antigen 4 and inhibit ligand binding. Conclusion: Phosphorylation on both the ␣ and ␤ chains of ␤ 2 integrins are needed, but the signal is transmitted through the ␤ 2 chain, leading to dephosphorylation of ␤ 1 . Significance: Our findings show a mechanism of integrin cross-talk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
(48 reference statements)
0
24
1
Order By: Relevance
“…We have previously shown that activation of LFA-1 through the TCR receptor or chemokine receptors, induces a signaling pathway, leading to the phosphorylation of Thr-758 on the b 2 -chain, 14-3-3 and Tiam1 binding, [14][15][16]19 and downregulation of a 4 b 1 binding to VCAM-1. 13 We have now found that activating and inhibitory antibodies to LFA-1 can regulate this signaling pathway. We collected antibodies to both b 2 and a L , which have been described to activate, inhibit, or have no effect on LFA-1 ligand binding (Table 1).…”
Section: Cell Adhesion and Migration Assaysmentioning
confidence: 92%
See 4 more Smart Citations
“…We have previously shown that activation of LFA-1 through the TCR receptor or chemokine receptors, induces a signaling pathway, leading to the phosphorylation of Thr-758 on the b 2 -chain, 14-3-3 and Tiam1 binding, [14][15][16]19 and downregulation of a 4 b 1 binding to VCAM-1. 13 We have now found that activating and inhibitory antibodies to LFA-1 can regulate this signaling pathway. We collected antibodies to both b 2 and a L , which have been described to activate, inhibit, or have no effect on LFA-1 ligand binding (Table 1).…”
Section: Cell Adhesion and Migration Assaysmentioning
confidence: 92%
“…Jb2.7 expressing wt LFA-1 has been described. 13 Naive T cells were purified from buffy coats obtained from the Finnish Red Cross Blood Transfusion Service (Helsinki, Finland) by Ficoll-Hypaque gradient centrifugation and nylon-wool columns. T blasts were induced by ImmunoCult human CD3/CD28/CD2 T-cell activator and 30 IU/mL IL-2 in ImmunoCult-XF T Cell Expansion Medium (Stemcell Technologies, Grenoble, France) and used after 96 hours.…”
Section: Cell Cultures Immunoprecipitation and Immunoblottingmentioning
confidence: 99%
See 3 more Smart Citations